2011
DOI: 10.1002/elps.201100413
|View full text |Cite
|
Sign up to set email alerts
|

Parallel single‐cell analysis microfluidic platform

Abstract: We report a PDMS microfluidic platform for parallel single-cell analysis (PaSCAl) as a powerful tool to decipher the heterogeneity found in cell populations. Cells are trapped individually in dedicated pockets, and thereafter, a number of invasive or non-invasive analysis schemes are performed. First, we report single-cell trapping in a fast (2-5  min) and reproducible manner with a single-cell capture yield of 85% using two cell lines (P3x63Ag8 and MCF-7), employing a protocol which is scalable and easily ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
(42 reference statements)
0
32
0
Order By: Relevance
“…Due to their miniaturization and automation, there are a number of advantages of using microfluidic systems, such as less sample/reagent consumption, reduced risk of contamination, less cost per analysis, lower power consumption, enhanced sensitivity and specificity, and higher reliability. Microfluidic systems have been developed for various biological analytical applications, such as DNA analysis [4][5][6][7][8], immunoassay [9][10][11][12][13], and cell analysis [14][15][16][17][18]. Moreover, a number of demonstrations showed that cell culture can be performed on the microfluidic systems to achieve higher throughput and more reliable results [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their miniaturization and automation, there are a number of advantages of using microfluidic systems, such as less sample/reagent consumption, reduced risk of contamination, less cost per analysis, lower power consumption, enhanced sensitivity and specificity, and higher reliability. Microfluidic systems have been developed for various biological analytical applications, such as DNA analysis [4][5][6][7][8], immunoassay [9][10][11][12][13], and cell analysis [14][15][16][17][18]. Moreover, a number of demonstrations showed that cell culture can be performed on the microfluidic systems to achieve higher throughput and more reliable results [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Several other methods have also been coupled with microfluidics for cell immobilization and conducting controlled, complete cell assays. Flow-based active cell trapping by using control valves [14,15], non-invasive optical trapping [16][17][18], dielectrophoresis [19][20][21], surface chemistry modification techniques [22,23], arrays of physical barriers [24], cell trapping by negative pressure [25,26], and hydrodynamic methods [27][28][29] are some of these successfully established techniques.…”
Section: Introductionmentioning
confidence: 99%
“…This system has shown great potential not only in sample manipulation and handling but also created a reputation for itself in being able to integrate multiparametric analysis in single platforms. LOC microfluidic devices have found a major niche in various facets of biochemical research including drug discovery [2,3], diagnostics [4][5][6][7][8], single cell analysis [9][10][11], single molecule detection [12][13][14], chemical synthesis [15,16], and other biological and chemical assays [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%